Biometric Based Home Security System - Modupalli Joshna, Chilamakuri Manisha, Yenigala Mohith, Konakondla Karthik Kashyap, Archana S Nadhan (International Journal of Control and Automation, 2020)
Nowadays, the use of IoT technology has developed that nearly all aspects of human life utilize IoT technology to extend the standard of life. once it involves our house, this idea may be capably incorporated to create it smarter, safer and automatic. Using Raspberry pi we can unlock/lock the main door using biometric fingerprint through a mobile phone app and we can also secure the cabins and internal doors of a house with RFID tags which are effortless of carrying a bunch of keys. As everything is interlinked to the internet it is more important to provide security to the home network and that can be done by using Pi-Hole which filters out the malware and ads containing on the home network.